Manifestaciones otorrinolaringológicas en la enfermedad de Takayasu - Nazar S., Rodolfo; Fullá O., Juan; Albertz A., Nicolás; Naser G., Alfredo (Revista Hospital Clínico Universidad de Chile, 2008)
Takayasu arteritis is a chronic idiopathic granulomatous vasculitis, which affects the aorta and its major branches, causing narrowing of the vascular lumen, which explains his particular symptoms. In children, its main manifestations are hypertension, cardiomegaly, increasing of the erythrocyte sedimentation rate, among others. We present a case of a girl aged 16, who has a long history of ozena. At physical examination there are nasal scabs and cacosmia. In the laboratory study highlights high levels of C Reactive Protein and erythrocyte sedimentation rate. The study through angio-Tac, shows a significant narrowing of supraaortic vascular structures.